The direct and indirect effects of China's wastewater treatment service on urban household wastewater discharge. (27th July 2020) - Zheng, Jiajia; Kamal, Muhammad Abdul; Ullah, Assad
Abstract: Urban household wastewater has surged with the urbanization in China, treatment of which demands attention. Utilizing China's urban panel data from 2005 to 2015, this article evaluates whether governmental wastewater treatment service changes urban residents' wastewater‐discharging behaviors. The outcomes reveal that: (a) in the short‐run when the local government treats more wastewater, the residents discharge more wastewater; (b) this short‐run relationship is notably strengthened by household attributes, that is, income and education; (c) in the long‐run, the increasing relationship between household wastewater discharge and wastewater treatment service also exists significantly, which calls for immediate attention of policy makers.